Geriatric assessment in hematology scale predicts treatment tolerability in older patients diagnosed with hematological malignancies: The RETROGAH study. Issue 1 (January 2023) - de la Rubia, Javier; González, Bernardo; Cruz-Jentoft, Alfonso J.; Iglesias, Lorena; Jarque, Isidro; Persona, Ernesto Pérez; Lluch, Rafael; Marrero, Carmen; Zudaire, Maite; Gironella, Mercedes; Hernández-Rivas, José Ángel; Arnan, Montserrat; et al.
Abstract: Introduction: The GAH (Geriatric Assessment in Hematology) scale is a psychometrically valid tool aimed at identifying older patients with hematological malignancies at higher risk of treatment-related toxicity. Our objective in this study was to determine the weights for each dimension of the GAH scale and the cut-off point to reliably predict treatment tolerability in this population, estimated by a weighted receiver operating characteristic (ROC) analysis and quantified by the area under the curve (AUC). Material and Methods: The RETROGAH was a retrospective cohort study including 126 patients who had previously participated in the GAH study. Patients were ≥ 65 years old with newly diagnosed myelodysplastic syndrome (MDS)/acute myeloid leukemia (AML), multiple myeloma (MM), or chronic lymphoid leukemia (CLL) and treated with standard front-line therapy within three months after having completed the GAH scale. Results: The optimal cut-off value of the GAH total score to discriminate patients at higher risk of treatment toxicity was 42, with 68.5% sensitivity and 55.8% specificity. Using this value, 66.1% of patients evaluated were found to develop some type of toxicity. The AUC was 0.6259 (95% CI: 0.512–0.739; p = 0.035). Discussion: The GAH scale not only would enable clinicians to individualize therapy based on individual risk of toxicity but also discriminate patients that will benefit most from intensive treatments from those requiring an adapted approach. While futures studies in clinical practice may improve the model and overcome its limitations, the GAH scale should not be used alone when making treatment decisions.